Kounis syndrome triggered by diclofenac sodium injection which leads to myocardial infarction and cardiac arrest - Cagliyan, Caglar Emre (J Cardiol Cases, 2013)
Allergic reactions due to drugs may lead to different clinical conditions. Acute coronary syndromes triggered by Type 1 hypersensitivity reactions due to drug intake are known as “Kounis syndrome.” Vasospasm occurring in normal coronary arteries (Type 1) and plaque rupture (Type 2) are two variants of this syndrome; both caused by vasoactive and inflammatory mediators due to hypersensitivity reaction. In this case report, we will present Type 2 Kounis syndrome leading to acute anterior myocardial infarction and cardiac arrest in a healthy male after diclofenac sodium injection via intramuscular route. <Learning objective: Incidence of Kounis syndrome due to diclofenac is higher than reported. Some of the myocardial infarction events referred to in the studies might be due to Kounis syndrome. The risk of myocardial infarction probability due to allergic reactions after intake of these drugs must be kept in mind when prescribing.>